Managing film and video collections (Aslib LondonGB, 1999)
Gives advice on how to deal with a wide range of physical formats viz. everything from 35mm monochrome film to images stored as digital files. Includes recommendations on the correct storage conditions and handling techniques needed to maximise preservation of the material : technical issues associated with managing a visual resource; documentation and techniques of cataloguing and indexing; how best to research the media and handle enquires, either to extract information, or to retrieve the actual physical items so that these can be used as a complete entity or as a part of a new project. Considers the impact of digitisation and the delivery of the media using the World Web Web.
Keywords: FILMS